Hydrofeminist Thinking with Oceans: Political and Scholarly Possibilities - Canham, Hugo ka (Critical Studies in Teaching and Learning, 2025)
Shefer, T., Bozalek, V. and Romano, N. (Eds.). 2024 Hydrofeminist Thinking with Oceans: Political and Scholarly Possibilities. London: Routledge. ISBN: 9781032408996